(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Afield experiment on French bean was conducted in Old Brahmaputra Floodplain Soil of Jamalpur and Grey Terrace Soil of Joydebpur during 2005-2006 to find out the optimum rates of N and P for yield maximization. Four levels of nitrogen (0, 100, 150 and 200 kg ha-1) and 3 levels of phosphorus (0, 40 and 60 kg ha-1) were used in the experiment. Potassium (K) 80 kg, sulphur (S) 10 kg and 5 t cowdung ha-1 were applied as a basal dose. The experiment was laid out in a randomized complete block design with 12 treatments replicated 4 times. Nitrogen and phosphorus alone significantly influenced the pod yield of French bean. Among the N levels, the highest pod yield (13.33 t ha-1 at Jamalpur and 14.68 t ha-1 at Joydebpur) were obtained with 150 kg N ha-1. Among the P levels, the highest pod yield (12.35 t ha-1 at Jamalpur and 13.69 t ha-1 at Joydebpur) were obtained with 60 kg P ha-1. Interaction effect was not significant. However, highest pod yield (13.60 t ha-1 at Jamalpur and 15.05 t h-1 at Joydebpur) was obtained from 150 kg N plus 60 kg P ha-1. Economic analysis showed that 150 kg N plus 40 kg P ha-1 gave the highest gross margin of Tk. 1,66,684/ha. Key words: French bean; Nitrogen and phosphorus fertilization; Pod yield DOI: 10.3329/bjsir.v45i2.5716 Bangladesh J. Sci. Ind. Res. 45(2), 169-172, 2010